Local manufacturing multiplier and human capital in Italian local labor markets - Marta Auricchio (European Regional Science Association (ERSA), 2015)
This paper quantifies the effect of a local labor demand shock in the tradable sector on the employment in the non-tradable sector for Italy. Following Moretti (2010) and Moretti and Thulin (2013) we analyse for Italy?s case the effect on the employment in tradable and non-tradable sector due to an exogenous shift in the number of jobs in the tradable sector in local labor market area. Using Italian census data at LLM level for 1991, 2001 and 2011, evidences suggest that, on average, the effect of an exogenous shift in local tradable employment upon non-tradable employment is zero. We believe that in this baseline model the absence of evidence of a positive impact of new jobs in the tradable sectors on the remaining parts of the local economy can be explained in particular focusing on excess of regulation, on labor mobility, on the lack of variability of wages, on the rigidity of housing supply and on the Italian familistic welfare system. In addition to the baseline model, we account for the technology level of the manufacturing sector using the EUROSTAT classification. We want to test if the jobs multiplier effect in the high-tech sector is significantly different/higher than for almost any other sector. High-tech workers, with their high opportunity cost of time, are expected to be net buyers of non-tradable goods. Accounting for the technology level, as Moretti, Moretti and Thulin predict, we find evidence that high-tech jobs have a positive and significant local employment multiplier of 2.2 additional jobs. These results bear important implications for the Italian growth path and its regional divide in terms both of labor market and industry competitiveness.
Keywords: R11; R12; 330; local labor market; multiplier; tradable non tradable